2023
DOI: 10.3390/molecules28031507
|View full text |Cite
|
Sign up to set email alerts
|

Improved Antioxidant and Mechanical Properties of Food Packaging Films Based on Chitosan/Deep Eutectic Solvent, Containing Açaí-Filled Microcapsules

Abstract: The development of biobased antioxidant active packaging has been valued by the food industry for complying with environmental and food waste concerns. In this work, physicochemical properties for chitosan composite films as a potential active food packaging were investigated. Chitosan films were prepared by solution casting, plasticized with a 1:2 choline chloride: glycerol mixture as a deep eutectic solvent (DES) and incorporated with 0–10% of optimized açaí oil polyelectrolyte complexes (PECs). Scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 78 publications
2
11
0
Order By: Relevance
“…Furthermore, it has been demonstrated that açaí leaf and root extract contain several phenolic hydroxycinnamic acid compounds, including 3- O -caffeoylquinic acid, 4- O -caffeoylquinic acid, and 5- O -caffeoylquinic acid [ 41 ]. Açaí root, in particular, contains other hydroxycinnamic acids, such as 3- O -caffeoylshikimic acid, 4- O -caffeoylshikimic acid, and 5- O -caffeoylshikimic acid ( Figure 6 ).…”
Section: Phytochemical Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been demonstrated that açaí leaf and root extract contain several phenolic hydroxycinnamic acid compounds, including 3- O -caffeoylquinic acid, 4- O -caffeoylquinic acid, and 5- O -caffeoylquinic acid [ 41 ]. Açaí root, in particular, contains other hydroxycinnamic acids, such as 3- O -caffeoylshikimic acid, 4- O -caffeoylshikimic acid, and 5- O -caffeoylshikimic acid ( Figure 6 ).…”
Section: Phytochemical Profilesmentioning
confidence: 99%
“…Among the health implications of açaí included in this discussion, antioxidant and anti-inflammatory faculties have been documented most frequently in the current literature. A large quantity of in vitro evidence exists in support of the antioxidant capacity of several compounds (e.g., polyphenols, flavonoids, anthocyanins) present in açaí [ 41 , 42 , 142 , 143 ]. Brunschwig et al [ 42 ] evaluated the in vitro antioxidant effect of açaí root and leaflet extracts using ferric reducing antioxidant power (FRAP), oxygen radical absorption capacity (ORAC), and 2,2-diphenyl-1-picrylhydrazyl (DPPH) tests.…”
Section: Biological and Pharmacological Effectsmentioning
confidence: 99%
“…The introduction of the special structure of the adsorbent, such as the interaction with the functional dye groups, can improve the selectivity of the adsorbent. Because of its specific surface area and water stability, microcapsules [ 28 , 29 , 30 ] have been successfully used for dye adsorption. As an adsorbent material, microcapsules can remove a variety of dyes in wastewater well because of their two advantages: one is to offer adsorption sites; the second is the quasi-spherical hollow structure of microcapsules.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] Most of such materials are chitosan-based films obtained in DES bearing carboxylic acids as HBD. [34][35][36][37][38][39][40][41] In general, these films can be obtained from the chitosan and the DES, or further doped with added external antioxidants, like, for instance quercetin 37 or naturally occurring flavonoids. 39 To the best of our knowledge, to date there is only one report on chitosan-based antioxidant gels and films obtained with DES having HBA different from carboxylic acids, namely glycerol.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41] In general, these films can be obtained from the chitosan and the DES, or further doped with added external antioxidants, like, for instance quercetin 37 or naturally occurring flavonoids. 39 To the best of our knowledge, to date there is only one report on chitosan-based antioxidant gels and films obtained with DES having HBA different from carboxylic acids, namely glycerol. 39 Using different HBDs for the DES can significantly expand the range of properties of the ensuing materials.…”
Section: Introductionmentioning
confidence: 99%